2017
DOI: 10.1186/s13643-016-0398-y
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of HIV transmission in out of school young heterosexual men in South Africa: a systematic scoping review protocol

Abstract: BackgroundIn South Africa, gender inequality dominated by males and heterosexual HIV epidemic are associated with high HIV infection. Underlying epidemiological and social determinants driving HIV acquisition and transmission are critical to understand the extent and complexity of sexual networks as primary mechanisms through which HIV is likely to spread. The aim of the study is to provide an overview of empiric evidence that links the complex interaction of risk of HIV infection in men.Methods and analysisWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Only 65% of participants who were sexually active knew their HIV status, which is considerably lower than the 90-90-90 UNAIDS initiative to ensure that 90% of the population know their HIV status. 32 A recent study by Ntombela et al has reported on research outcomes which suggest that being black African male, having low levels of education, being from a rural area and being unemployed are all associated with lower knowledge of one's own HIV status, 33 and increase HIV risk behaviours in men. 34 It was of concern that just over a third of those who were sexually active were knowledgeable about their partner's HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…Only 65% of participants who were sexually active knew their HIV status, which is considerably lower than the 90-90-90 UNAIDS initiative to ensure that 90% of the population know their HIV status. 32 A recent study by Ntombela et al has reported on research outcomes which suggest that being black African male, having low levels of education, being from a rural area and being unemployed are all associated with lower knowledge of one's own HIV status, 33 and increase HIV risk behaviours in men. 34 It was of concern that just over a third of those who were sexually active were knowledgeable about their partner's HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is a systematic scoping review which was registered in the international prospective register of systematic reviews (PROSPERO). The registration number of the review is CRD42016039489 and is accessible via this link https://systematicreviewsjournal.biomedcentral.com/articles/10.1186/s13643-016-0398-y (Ntombela, Mashamba-Thompson, Mtshali, Voce, & Kharsany, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Scoping reviews are essential in comprehensive synthesis of evidence of a range of study designs (O'Brien et al, 2016), with aims to i) Assess the extent, range and nature of evidence on the literature on the topic, ii) to establish the need of conducting a systematic review, iii) to summarize and disseminate research findings and lastly iv) to identify gaps in literature on the topic. We used an amended version of a scoping review protocol described by Ntombela et al, (Ntombela et al, 2017). Briefly, we adopted a framework by Arksey, H., and O'Malley (Arksey & O'Malley, 2005).…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations